Emotions and Motivation from the Perspective of Science and Religion - Diah Ayuni; Qorina Rahmatika (Yayasan Insan Cendekia Nusantara, 2024)
Every human being must have emotions and motivation to survive because both have such a big influence. Emotions and motivation have their own meanings and theories from the perspective of Science and religion. If the two are linked then the power of a person to act is higher, both positive and negative actions. Emotions and motivation also affect the components of human physiology. It is arranged so that humans can control their actions in the life of the nation and state. The main factors of human needs, both physical and non-physical, are influenced by emotions and motivations arising from the human being. Emotions often do not appear physically but can be seen through the way a person behaves. Therefore, emotions are difficult to describe. The same applies to motivation, which is the background for a person's actions to meet the desired goal. Actions performed based on motivation are also performed consciously. This article was created to find out the scientific understanding of emotions and motivation from the point of view of Science and religion